Phylosophy of science (plus ethics in research) - Rohana, Hamzah; Zuraina, Ali (Penerbit UMP, 2017)
This module provides an overview concerning the philosophy of science and how it relates with the purpose of knowledge development process through education. It introduces the concept of philosophy and its underlying questions. It is crucial to understand this concept because knowledge development through R&D occurs intensively at higher education level. Therefore, this module will discuss the reality of existence, epistemology of knowledge, ethics and aesthetic and the inter-connection between the topics. Knowledge or science development process that is not properly guided or fails to consider ethical issues will result in making it worthless.